Quantifying the Changes of Mechanical and Electrical Properties of Paralyzed Muscle in Survivors With Cervical Spinal Cord Injury - Hu, Huijing; Chen, Yingyue; Wang, Xiaoyun; Lo, Wai Leung Ambrose; Li, Le (Frontiers in Neurology, 2021)
Abstract Background: Survivors with spinal cord injury (SCI) have neuromuscular deficits such as muscle atrophy that lead to functional impairments. This study utilized myotonometry and electrical impedance myography (EIM) to quantitatively evaluate the changes of muscle mechanical properties and compositions after SCI. Methods: This study adopted a cross-sectional design. 18 SCI patients and 18 healthy individuals were recruited. Outcome measures were: 1) myotonometer measured muscle mechanical parameters of oscillation frequency (freq), dynamic stiffness, logarithmic decrement (decr), mechanical stress relaxation time and indication of creep; 2) electrical impedance myography measured parameters of resistance (R), reactance (X) and phase angle (θ); 3) muscle strength (maxForce); 4) clinical scales of Manual Muscle Testing (MMT) and modified Ashworth scale (MAS). All outcome measures were compared between the bicep brachii muscle of the weaker side of the SCI group and the non-dominate side of the healthy group. Correlation analysis was performed at quantitative data and clinical scales. Results: Freq, stiffness and maxForce of the SCI group were significantly lower (p<0.01) than the healthy control. The relaxation time and creep were significantly higher in the SCI group than the control group. Significant differences of R and Xc were observed between the two groups. Significant correlation was observed between freq, stiffness and months past injury, and between Xc, creep and relaxation time. Conclusions: Reduced muscle tone and stiffness might relate to muscle atrophy, and higher relax time and creep may be caused by poor contractile ability. The changes in EIM parameters could indirectly reflect the muscle cell size, fatty and connective tissue alterations. These findings support the feasibility of myotonometer and EIM to quantify muscle mechanical and intrinsic properties in patients with SCI. The results could facilitate the understandings neuromuscular changes that are related to functional impairments.